(untitled) (Research, Society and Development, 2023)
In the context of teacher education, environmental education and health education are interdisciplinary fields that can contribute, together, to teacher training and the formation of critical and ethical citizens. This review protocol aims to map the scientific evidence, through the scope review method, in scientific articles, on environmental education and health education in the context of teacher training. The protocol was prepared based on the guidelines of the Joanna Briggs Institute (IJB), it will meet the recommendations of the Preferred Reporting Items for Systematic and Meta-Analyses - Extension for Scoping Reviews (PRISMA-ScR). The data extracted in this research will be summarized and presented in the format of a scientific article.